DEVICE DRIVER FOR 3-AXIS ACCELEROMETER BASED ON ARM CORTEX-M0+ PROCESSOR - Patel, Zuber M (MATTER: International Journal of Science and Technology, 2018)
The use of accelerometers in aerial vehicles is crucial for measuring tilt (inclination) in order to control hovering. In this work, the driver software for 3-axis accelerometer device is developed based on the platform of ARM cortex M0+ processor. This driver software reads the values of acceleration of all 3 axes and computes roll, pitch and yaw tilt angles. This driver software is then integrated to open source freeRTOS operating system and then complete system using freeRTOS is tested by making system call from application software.